The impact of tariff diversity on broadband diffusion: An empirical analysis - Justus Haucap; Ulrich Heimeshoff; Mirjam R. J. Lange (International Telecommunications Society (ITS), 2014)
This paper provides an empirical analysis how tariff diversity affects broadband uptake, utilizing a new data set with 1497 fixed-line and 2158 mobile broadband tariffs from 91 countries across the globe. An instrumental variable approach is applied to estimate the demand for fixed broadband internet access, controlling for various industry and socio-economic factors. The empirical results indicate that, first, in addition to lower prices and higher income, more tariff diversity additionally increases broadband penetration. Secondly, inter-platform competition and mobile broadband prices are not found to have a significant effect on fixed-line broadband penetration. This suggests that low prices, higher incomes and the diversity of broadband offerings are more important drivers of fixed broadband adoption than competition between various technologies (cable networks, fixed-line telephone networks, mobile networks).
Keywords: L86; L96; 330; Broadband prices; Tariff diversity; Broadband demand; Broadband penetration; Broadband uptake; Price discrimination; Inter-platform competition